Penyebaran Konten Ilegal di Internet: Tinjauan Yuridis terhadap Regulasi, Penegakan, dan Harmonisasi Hukum di Indonesia - Gilang Rizki Aji Putra (BULETIN ADALAH, 2023)
The dissemination of illegal content on the internet represents a disruptive phenomenon that threatens public order, morality, and national security. This article provides a juridical review of Indonesia’s legal framework in addressing illegal online content, examining regulatory instruments, enforcement challenges, and the urgency of legal harmonization. Employing normative legal research with statutory, conceptual, and comparative approaches, the study finds that Indonesia’s regulatory regime remains fragmented across various sectoral laws, including the Electronic Information and Transactions Law (ITE Law), the Pornography Law, the Child Protection Law, and the Penal Code. This fragmentation creates overlapping norms, legal uncertainty, and the risk of criminalizing legitimate expression. Analysis of cases involving hate speech, pornography, and disinformation highlights the tension between effective enforcement and human rights protection. Cross-border jurisdictional issues and reliance on foreign platforms further complicate enforcement. The article concludes that regulatory harmonization, stronger due process safeguards in content blocking, and ratification of the Budapest Convention are essential for a fair and secure digital ecosystem. Keywords: Illegal Content, Electronic Information and Transactions Law (ITE Law), Legal Harmonization, Content Blocking, Digital Jurisdiction.